156 Prehospital determinants of successful resuscitation after traumatic and non-traumatic out-of-hospital cardiac arrest. Issue 12 (23rd November 2020) - Barnard, Ed; Sandbach, Daniel; Nicholls, Tracy; Wilson, Alastair; Ercole, Ari
Abstract : Aims/Objectives/Background: Out-of-hospital cardiac arrest (OHCA) is prevalent in the UK. Reported survival is lower than in countries with comparable healthcare systems; a better understanding of outcome determinants may identify areas for improvement. Aim: to compare differential determinants of survival to hospital admission and survival to hospital discharge for traumatic (TCA) and non-traumatic cardiac arrest (NCTA). Methods/Design: An analysis of 9109 OHCA in East of England between 1 January 2015 and 31 July 2017. Univariate descriptives and multivariable analysis were used to understand the determinants of survival for NTCA and TCA. Two Utstein outcome variables were used: survival to hospital admission and hospital discharge. Data reported as number (percentage), number (percentage (95% CI)) and median (IQR) as appropriate. Continuous data have been analysed with a Mann-Whitney U test, and categorical data have been analysed with a χ2 test. Analyses were performed using the R statistical programming language. Results/Conclusions: The incidence of OHCA was 55.1 per 100 000 population/year. The overall survival to hospital admission was 27.6% (95%CI 26.7% to 28.6%) and the overall survival to discharge was 7.9% (95%CI 7.3% to 8.5%). Survival to hospital admission and survival to hospital discharge were both greater in the NTCA group compared with the TCA group: 27.9% vs 19.3% p=0.001, and 8.0% vs 3.8% p=0.012 respectively. Determinants of NTCA and TCA survival were different, and varied according to the outcome examined. In NTCA, bystander cardiopulmonary resuscitation (CPR) was associated with survival at discharge but not at admission, and the likelihood of bystander-CPR was dependent on geographical socioeconomic status. NTCA and TCA are clinically distinct entities with different predictors for outcome and should be reported separately. Determinants of survival to hospital admission and discharge differ in a way that likely reflects the determinants of neurological injury. Bystander CPR public engagement may be best focused in more deprived areas.